English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! The relationship between how words are pronounced and how they are spelled is often unpredictable. In addition, many of us don't know when words should be capitalized. In this program, you'll learn simple rules that can instantly improve your spelling and capitalization, which words are "exceptions," and how to distinguish between often-confused words! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever.